The future of the Internet and how to stop it - Zittrain, Jonathan 1969- (Jonathan L.); Lessig, Lawrence Prefaciador (New Haven, Conn. : Yale University Press, 2008)
Pt. I. The rise and stall of the generative Net -- 1. Battle of the boxes -- 2. Battle of the networks -- 3. Cybersecurity and the generative dilemma -- Pt. II. After the stall -- 4. The generative pattern -- 5. Tethered appliances, software as service, and perfect enforcement -- 6. The lessons of Wikipedia -- Pt. III. Solutions -- 7. Stopping the future of the Internet : stability on a generative Net -- 8. Strategies for a generative future -- 9. Meeting the risks of generativity : Privacy 2.0.